(untitled) (Altre Modernità, 2010)
Death is an overarching presence in Sarah Kane’s dramatic universe, peopled by characters charging towards death, and usually encountering it in scenes of Grand Guignol excess and grotesque violence. Death is ambivalently presented as the only escape from the nightmare of living and, at the same time, as that which makes living a nightmare; as the moment of "complete sanity and humanity" in which "everything suddenly connects", and as the ultimate, irrevocable and unredeemable act of self-annihilation. Following Kane’s turn towards a more poetic form of drama, in her last two plays this discourse of death is handed over to the words nameless characters or unidentified voices who are likewise engaged in a long, painful quest for selfhood pivoting on the awareness of mortality and the simultaneous dread of and longing for death it engenders. This essay focuses on the ritual quality of the death scenes and/or narratives that crowd Kane’s drama. Throughout her work, dying is never an easy, straightforward business, but rather a long, complicated, and at times frustrating mise en scène which also entails rehearsing a repertory of traditional rituals and, once their shortcomings become apparent, devising and testing new ones. The amount of theatricality involved in the art of dying is foregrounded through a web of intertextual references to other literary and/or dramatic sources; this dialogue ties in with a self-reflexive probing of the theatre’s ability to provide a ritual that will be capable of "contain[ing] the horror" by supplying a formal framework to express, embody and experience death collectively.